Synopsis of the bark and ambrosia beetles of West Malaysia (Coleoptera: Curculionidae: Scolytinae) - Smith, Sarah M.; Beaver, Roger A.; Ong, Su Ping; Cognato, Anthony I. (Zootaxa, 2025)
A checklist of the West Malaysian fauna is provided with information on local and world distribution, host trees, biology and taxonomy. Three hundred seventy-six species are recorded from Malaya, 33 for the first time. Five new species are described: Asiophilus bukiticola Smith, Beaver & Cognato sp. nov., Cyclorhipidion brownei Smith, Beaver & Cognato sp. nov., Euwallacea frimensis Smith, Beaver & Cognato sp. nov., Euwallacea phrixosoma Smith, Beaver & Cognato sp. nov., and Microperus pasohanthus Smith, Beaver & Cognato sp. nov. Three species are removed from synonymy and reinstated as valid species: Euwallacea barbatus (Hagedorn, 1910), Euwallacea pseudobarbatus (Schedl, 1942), Euwallacea rudis (Eggers, 1930). Two new combinations are proposed: Ancipitis scabrior (Schedl) comb. nov. from Leptoxyleborus Wood, 1980; Xylosandrus mascareniformis (Eggers, 1972) comb. nov. from Xyleborus Eichhoff, 1864. Two new synonyms are proposed: Coccotrypes gedeanus (Eggers, 1936) (= Xyleborus despectus Schedl, 1975 syn. nov.) and Arixyleborus scapularis (Schedl, 1942) (=Xyleborus magnus Browne, 1985 syn. nov.).